2020
DOI: 10.29333/ajqr/8203
|View full text |Cite
|
Sign up to set email alerts
|

Appointment Robbery: Do Crime Prevention Through Environmental Design Strategies Work? Voices from the Street

Abstract: Crime Prevention Through Environmental Design (CPTED) theory posits that crime can be reduced with modifications and planning to the physical environment by making involvement in criminal activity more difficult to complete by increasing the visibility of the offender thereby raising the risk of being caught. A new type of criminal opportunity has evolved in the 21 st Century with the introduction and explosion of direct e-commerce opportunities with online and app advertisements to buy and sell items through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Natural surveillance is a component of CPTED, a principle of the environment’s ability to generate human opportunities to watch over one another (Molaei and Hashempour, 2020; Vasquez et al , 2020). Many studies have demonstrated that natural surveillance encourages authorised persons to use their demarcated spaces, arguing the inherent risk and difficulty of ensuing crime (Cozens et al , 2019; Cozens and Sun, 2019; Reynald, 2015; Shariati and Guerette, 2020, 2019).…”
Section: Crime Prevention Through Environmental Designmentioning
confidence: 99%
“…Natural surveillance is a component of CPTED, a principle of the environment’s ability to generate human opportunities to watch over one another (Molaei and Hashempour, 2020; Vasquez et al , 2020). Many studies have demonstrated that natural surveillance encourages authorised persons to use their demarcated spaces, arguing the inherent risk and difficulty of ensuing crime (Cozens et al , 2019; Cozens and Sun, 2019; Reynald, 2015; Shariati and Guerette, 2020, 2019).…”
Section: Crime Prevention Through Environmental Designmentioning
confidence: 99%
“…The gatekeeper was identified by the primary author, who was at the time a gang interventionist and had known him for five years. The gatekeeper was an individual who was active in robbery and had strong connections and reputation throughout criminal networks and who participated in different types of crime (Vasquez et al, 2020). The primary researcher asked the gatekeeper, Tito, to be introduced to people who were engaged in robberies.…”
Section: Samplingmentioning
confidence: 99%
“…The primary researcher asked the gatekeeper, Tito, to be introduced to people who were engaged in robberies. Due to Tito's strong reputation in the streets, it was easy for him to clarify the study objectives and to validate the researcher as a nonthreatening individual to the participant's social and legal status (Biernancki & Waldorf, 1981;DeShay et al, 2020, Irwin, 1972Vasquez et al, 2020;Vasquez & Vieraitis, 2016).…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The broader focus of CPTED is to highlight and encourage positive community ownership of a space and to support legitimate use of the space, while psychologically deterring potential offenders and preventing criminal activity. Research has shown that techniques of CPTED are best used early in the design stages so that the physical appearance of the area can be built to reduce criminal activity (Parnaby, 2007;Cozens & Love, 2015, Marzbali, Abdullah, Ignatius, Tilaki, 2016Armitage, 2018;Vasquez, Rodriguez, Suh, & Martinez-Cosio, 2019). Yet there remains a lack of clarity regarding a model that emphasizes which of CPTED's fundamental components actually works from the offender's perspective.…”
Section: Access Controlmentioning
confidence: 99%